1988
DOI: 10.2466/pr0.1988.62.1.268
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Identity among Sansei and Yonsei Church-Affiliated Youth in Los Angeles and Honolulu

Abstract: A comparative study of 112 Japanese-American Sansei and Yonsei youth in Los Angeles, California, and Honolulu, Hawaii—drawn from the rosters of youth active in Japanese-American church organizations—found no over-all differences by location, generation, or sex. Some significant differences, however, were noted for specific items. Of particular note are the shared (and continued) traditional values of these Los Angeles and Honolulu church-going Japanese-American youth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Traditionally, it has been suggested that immigrants invariably discarded the values of their culture of origin and accommodated to the mainstream host culture (Phinney, 1990;. Although this may have been possible (whether or not desirable) for European immigrants, it was more difficult for nonwhite Americans with backgrounds vastly different than that of European Americans (Wooden, Leon, & Toshima, 1988). With increasing awareness and appreciation for the growing cultural diversity in the United States, it has been postulated that instead of a linear perspective where endorsement of one culture necessarily implicated rejection of another, a two-dimensional approach may be more valid.…”
Section: Cultural Orientationmentioning
confidence: 99%
“…Traditionally, it has been suggested that immigrants invariably discarded the values of their culture of origin and accommodated to the mainstream host culture (Phinney, 1990;. Although this may have been possible (whether or not desirable) for European immigrants, it was more difficult for nonwhite Americans with backgrounds vastly different than that of European Americans (Wooden, Leon, & Toshima, 1988). With increasing awareness and appreciation for the growing cultural diversity in the United States, it has been postulated that instead of a linear perspective where endorsement of one culture necessarily implicated rejection of another, a two-dimensional approach may be more valid.…”
Section: Cultural Orientationmentioning
confidence: 99%
“…The incremental increase in acculturation from the earliest generation category (Issei) to the latest category (Yonsei) adds support for the face validity of the acculturation measure. In addition, the distinctions beyond third generation individuals tapers off, perhaps because Japanese Americans "have reached a point in history where changes in acculturation are minimal" (Wooden, Leon, & Toshima, 1988). In addition, the brief acculturation scale accounts for half of the variation in the full 21-item SL-ASIA.…”
Section: Factors Associated With Acculturationmentioning
confidence: 99%
“…Recently, a Hawaiian acculturation scale was developed as a cultural measure of Hawaiianess in addition to self-reported blood quantum measures (Rezentes, 1993 (Montgomery, 1992;Mendoza, 1989;Franco, 1983;Cuellar, 1980), Asians (Suinn, 1987), Japanese-Americans (Wooden, 1988;Newton, 1988) Navajo (Boyce, 1983), Israeli-born Jews (Dor-Shav, 1990), Greek Cypriot immigrants to London (Mavreas, 1989) and multiple ethnic groups (Phinney, 1992;Sodowsky, 1991;Wong-Rieger, 1987). …”
Section: Introductionmentioning
confidence: 99%